Aspek-Aspek Perancangan PLTB Untuk Penggunaan Rumah Tangga Di Kecamatan Tembilahan Hulu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tembilahan hulu is area which has a low wind speed with 4 m/s as a mean. Vertical axis wind (VAWT) turbine is more effective to low wind speed aplication with several advantages, can capture wind from any direction and simples in fabrication and cost. 3 blades H-Darrieus type is chosen for used. This paper is focused on a technique that can be used effectively for design and fabrication to developed wind turbine as a device to convert kinetic energy from wind to electrical power. Q-blade is used to simulation and determined parameter to design wind turbine. NACA 8612 used as airfoil with 0,21 m chord line and 40 angle of attack. Turbine has 0,4 m in height and 0,6 m diameter. Performence test show torque, rotational speed, power coefficient and mechanical power that can used to determine generator and accumulator for this system.Keywords: Low wind speed,vertical axis wind turbine,Darrieus, Q-blade